Immunity against a Chlamydia infection and disease may be determined by a balance of IL‐17 signaling. Issue 3 (24th December 2013) - O'Meara, Connor P; Armitage, Charles W; Harvie, Marina CG; Andrew, Dean W; Timms, Peter; Lycke, Nils Y; Beagley, Kenneth W
Abstract : Most vaccines developed against Chlamydia using animal models provide partial protection against a genital tract infection. However, protection against the oviduct pathology associated with infertility is highly variable and often has no defining immunological correlate. When comparing two adjuvants (CTA1‐DD and a combination of Cholera toxin plus CpG‐oligodeoxynucleotide–CT/CpG) combined with the chlamydial major outer membrane protein (MOMP) antigen and delivered via the intranasal (IN), sublingual (SL) or transcutaneous (TC) routes, we identified two vaccine groups with contrasting outcomes following infection. SL immunization with MOMP/CTA1‐DD induced a 70% reduction in the incidence of oviduct pathology, without significantly altering the course of infection. Conversely, IN immunization with MOMP/CT/CpG prevented an ascending infection, but not the oviduct pathology. This anomaly presented a unique opportunity to study the mechanisms by which vaccines can prevent oviduct pathology, other than by controlling the infection. The IL‐17 signaling in the oviducts was found to associate with both the enhancement of immunity to infection and the development of oviduct pathology. This conflicting role of IL‐17 may provide some explanation for the discordance in protection between infection and disease and suggests that controlling immunopathology, as opposed to the rapid eradication of the infection, may be essential for an effective human chlamydial vaccine that prevents infertility.